ANALISIS SOAL UJIAN TENGAH SEMESTER MATA PELAJARAN BAHASA INDONESIA BERBASISI HIGHER ORDER THINKING SKILLS (HOTS) DI SMP KELAS VII - Adinda Nabila; Rosmaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the level of taxonomy bloom revision and characteristics of HOTS questions on UTS questions for Indonesian Class VII subjects SMP Negeri 4 Medan and SMP Negeri 6 Medan. Data used in the study this is about UTS Indonesian Class VII subjects from both schools such. The research method used is descriptive qualitative research with content analysis techniques. In SMP Negeri 4 Medan, UTs question consists of 35 items multiple choice and 5 descriptions. Results of analysis on multiple choice questions shows the distribution: (C1) 6 problems, (C2) 8 problems, (C3) 7 problems, and (C4) 9 problems, while C5 and C6 do not appear. The problem description consists of (C1) 3 questions and (C4) 2 questions. Distribution of the overall percentage of questions in SMP Negeri 4 Medan produce LOTS by 42%, MOTS by 25%, and HOTS by 31%, so that the proportion of LOTS overvalued with MOTS that are much lower than ideal. Analysis characteristics of HOTS questions in SMP Negeri 4 Medan includes 10 multiple choice questions (number 5, 7, 9, 10, 11, 14, 16, 22, 23, and 26) and 1 problem description (Number 5), with characteristic details: critical thinking 3 questions, divergent 3 questions, contextual based 4 problems, and 1 problem multipresentation. As for the SMP Negeri 6 Medan, about UTS only consists of 3 items description. The results of the analysis showed the distribution: (C3) 1 problem and (C6) 2 problem with the percentage distribution of LOTS 33%, MOTS 0%, and HOTS 66%. Composition this is judged unbalanced because MOTS do not appear at all and the proportion of HOTS too dominant. Characteristic analysis of problem HOTS in SMP Negeri 6 Medan include 2 problem description with details: critical thinking 2 problem, divergent O problem, based context 1 problem, and multipresentation 1 problem. In general, the whole point UTS Class VII of both schools have met the indicators and characteristics of the problem HOTS are set. However, the level of understanding of learners is not measured based on their ability to solve the problem of hot category.